Epistemologi Ilmu: Landasan Filsafat dalam Pengembangan Pengetahuan - Suryati, Heti (Yayasan Sembilan Pemuda Indonesia, 2025)
Philosophy of science plays an important role in building foundation for the development of science. In the context of education, epistemology, ontology, and axiology serve as key elements that form the framework for thinking in compiling and developing knowledge. that form the framework for thinking in compiling and developing science knowledge. This research aims to examine the relationship between the epistemological aspects of epistemology in the philosophy of science with the development of science, as well as how the application of the philosophy of science can enrich understanding in the development of science. how the application of philosophy of science can enrich understanding in various disciplines. scientific disciplines. The approach used in this research is a literature study by analyzing literature by analyzing literature related to the philosophy of science and key concepts such as ontology, epistemology, and epistemology. concepts such as ontology, epistemology, and axiology. The result of this research shows that a deeper understanding of these three aspects can strengthen the basis of scientific theories and broaden the scope of scientific disciplines. can strengthen the basis of scientific theories and broaden the scope of understanding of science, both in the field of education and in a broader social context. wider social context. Therefore, the proper application of the philosophy of science is expected to create a more holistic and evolving can create a science ecosystem that is more holistic and develops in accordance with the demands of the times. in accordance with the demands of the times.